A comparison of the effects of cobalt-60 γ ray irradiation on DPSA bipolar transistors at high and low injection levels. (April 2017) - Zhang, Peijian; Wu, Xue; Yi, Qianning; Chen, Wensuo; Yang, Yonghui; Zhu, Kunfeng; Tan, Kaizhou; Zhong, Yi
Abstract: We investigate the γ-ray total dose induced degradation of double polysilicon self-aligned (DPSA) bipolar NPN transistors at low dose rate. Through comparing the measured results in low- and high-level injection regions, we find that the main irradiation damages related defects in two regions are quite different. In the case of lower emitter-base (E-B) bias, the damage is mainly localized in E-B interface region. For high-level injection, excess base current mainly results from radiation induced defects in intrinsic base region. Furthermore, a phenomenological model based on qualitatively analytical calculation is adopted to explain the experimental results. Highlights: Radiation damage is mainly localized in E-B interface region. The damage related defects in two injection regions are quite different. A phenomenological model is adopted to explain the experimental results.